Review on the contribution of ultrasounds in layered double hydroxides synthesis and in their performances - Kalawoun, Hamed; Obeid, Michel; Ciotonea, Carmen; Chaghouri, Muriel; Poupin, Christophe; Aouad, Samer; Labaki, Madona; Gennequin, Cédric; Abi-Aad, Edmond; Delattre, François (Comptes Rendus. Chimie)
Layered double hydroxides (LDHs) are promising because of some of their several interesting characteristics. LDHs can be synthesized using different preparation methods. The application of ultrasounds (US) in the preparation method leads to reduced synthesis times and better dispersion of particles characterized by small size and narrower particle size distribution. Consequently, the specific surface area is higher in US-prepared samples compared to materials prepared by classical methods. These modified characteristics are responsible for improving the performances of LDHs used as catalyst precursors, adsorbents of dyes and heavy metals, fire suppressants, and other applications.